Comparison of the quality of three obturation techniques in primary anterior teeth using cone-beam computed tomography: An in vitro study - Alaa F Irzooqi; Aseel Haider M J Al Haidar; Maisaa QM Ali; Omar A Bawazir (College of Dentistry/ University of Baghdad, 2024)
Background: This study aimed to compare the number of voids of primary anterior teeth obturated with Endoflas by using three different obturation techniques, namely, endodontic pressure syringe, modified disposable syringe, and reamer using cone-beam computed tomography (CBCT). Materials and Methods: Thirty-six single-rooted primary incisors and canines with lengths ranging within 15-22 mm were randomly divided into three groups (12 teeth/group) according to the obturation techniques used. Group A, endodontic pressure syringe; group B, modified disposable syringe; and group C, reamer. A single operator instrumented and obturated all teeth by using Endoflas. An independent evaluator analysed the quality of the obturation techniques by using CBCT imaging to determine the number of voids in the root canals. Fisher's exact test and multiple pairwise comparisons adjusted by the Dunn-Bonferroni method were used to statistically assess the results. Results: All study groups showed no statistically significant difference in the number of voids (P > 0.05). Comparing the thirds of each group, the coronal and middle thirds of group A contained the maximum number of voids, followed by groups B and C, with no statistically significant difference. For the apical third, voids were highly presented in group C followed by group B. Meanwhile, group A was found to have no voids. Conclusion: Within the limitations of the current research, we concluded that voids existed in all techniques used; however, they were the least when using endodontic pressure syringes. Thus, an endodontic pressure syringe used with an Endoflas obturation material may be preferred as an obturation technique.